A systematic review of interventions that impact alcohol and other drug-related harms in licensed entertainment settings and outdoor music festivals - Christopher Eassey; Caitlin E. Hughes; Phillip Wadds; Dominique de Andrade; Monica J. Barratt (BMC, 2024)
Abstract Background Harms associated with the use of alcohol and other drugs (AOD) in licensed entertainment settings (LES) and outdoor music festivals (OMF) are ongoing public health and criminal justice concerns. This systematic review provides a comprehensive, synthesized report on the evidence base of interventions that impact harm in these settings, and how they affect health, behavioral, and criminal justice outcomes. Methods Nine databases were searched for experimental and observational studies published between 2010 and 2021. Studies were included if they were peer-reviewed, published in English, described interventions which could impact AOD-related harms in LES or OMF (and were delivered in these environments), and reported on health, criminal justice and/or behavioral outcomes. Methodological quality was assessed using the Effective Public Health Practice Project's Quality Assessment Tool for Quantitative Studies and the Critical Appraisal Skills Program for qualitative studies. A narrative synthesis was conducted to synthesize outcomes across studies. The review protocol was registered in PROSPERO (CRD42020140004). Results Of the 48,303 studies screened, 100 met the inclusion criteria. 86 focused solely on reducing alcohol-related harm, 7 on reducing illicit drug-related harm, and 7 on both. Most (n = 88) focused on LES and evaluated changes in laws and regulations (n = 28) and/or multicomponent interventions/policies (n = 41). Multicomponent interventions showed the best results for both health (62% positive) and criminal justice (84% positive) outcomes, with 71% of studies being rated as strong quality. There was also good evidence to support the careful application of trading hour restrictions and limited but promising evidence to support medical services and drug checking. Conclusion The breadth, quality and volume of evidence regarding what works in reducing AOD-related harm in recreational settings have increased in the past decade, particularly regarding LES. Findings support onsite medical services (reducing ambulance transfer rates), multicomponent interventions targeting alcohol accessibility and availability (reducing assaults), and drug checking services, but suggest other interventions such as drug detection dogs may exacerbate harm. Further, higher quality research is required to address identified gaps in the evidence base, particularly on optimal interventions within OMF, around illicit drugs more broadly and in the Global South.